Total urokinase-type plasminogen activator (uPA) levels in seminal plasma are associated with positive assisted reproductive technology outcomes - Martinez-Soto, Juan Carlos (J Assist Reprod Genet, 2018)
PURPOSE: The plasminogen/plasmin system is an important extracellular protease system whose function has been implicated in male reproductive function. However, its clinical relevance to fertility in human assisted reproduction technologies has not been systematically investigated. Here, we examined whether total and active populations of urokinase-type plasminogen activator (uPA) in human seminal plasma and spermatozoa are predictive of pregnancy outcome in couples undergoing insemination or intracytoplasmic sperm injection (ICSI). METHODS: Seminal samples from 182 men, 5 donors, 21 patients attending the clinic for infertility screening, and 156 for assisted reproduction technology (ART) treatment (insemination and ICSI), were evaluated. Total uPA in seminal plasma and spermatozoa as well as active uPA in seminal plasma were measured by ELISA. Sperm quality parameters and fertility outcomes following insemination or ICSI were correlated with the uPA values. RESULTS: Active uPA in seminal plasma was positively correlated to the volume of the ejaculate, total number of spermatozoa in the ejaculate, and total motility. However, these values were not prognostic of fertility outcomes. Total uPA in spermatozoa was inversely related to sperm concentration, total sperm in ejaculate, morphology, and total and progressive motility, and this measure was not related to fertility. Importantly, however, higher values of total uPA in seminal plasma were detected in cases that resulted in pregnancy compared to those that did not follow insemination and ICSI treatment. CONCLUSIONS: Taken together, these findings lay the foundation for further understanding the mechanism by which total uPA in seminal plasma affects fertility and how this marker can be used as a predictor of ART outcomes.